ARABIC: WHY INDONESIANS HAVE TO LEARN IT? - Letmiros, Letmiros (International Review of Humanities Studies, 2019)
Arabic has many virtues. The first virtue of Arabic is that it is part of Islam. Then, Arabic as one of the old languages in the world has an amazing history of civilization. Furthermore, Arabic is an international language that has been used as one of the official languages of the United Nations since 1973. Because of these advantages, Arabic is interesting to be studied and researched by non-Arabs including by Indonesians. Arabic is studied, in addition to the purpose or because of the factors of Islam, also because of the factors of world life, for the demands of work or profession and so forth. Arabic is also one of the three old languages in the world that still exists and is used in various fields of life. The close relationship between Indonesia and Arab countries, which numbered 22 countries, also encouraged Arabic to be studied by the Indonesian population. Arabic is a part of a language that is easily learned by anyone including Indonesian people. The teaching of Arabic as a foreign language is intended so that one can master this language from various aspects: listening, speaking, reading and writing. For Indonesians, the many similarities between the Indonesian and Arabic systems both at the level of phonology, morphology, syntax, and semantics will be enough to help them learn the language which includes Semito-Hamit field.